Performance comparison in combined events - de Freitas Anselmo, C. A.; Russomano, T. G. (Proceedings of First Joint International Pre-Olympic Conference of Sports Science and Sports Engineering. Volume I: Computer Science in Sports., 2008)
Combined events exist since ancient Greeks, who disputed the pentathlon (running, jumping, discus throw, javelin throw and wrestling). Nowadays, the decathlon, distributed in ten events, consecrates its champion as the all-round athlete. Decathlon is not the only competition disputed in a "combined events" way. We can list the famous adventure races and triathlons, as well as some less known, like modern pentathlon, Gigathlon and Multiathlon. In all these competitions, if the all-roundness is the objective, it's necessary to use a scoring model allowing compare performances in all events through a uniform manner. For this purpose, scoring tables have been developed for each of the events (in decathlon and other combined events in Athletics, like heptathlon). Despite of this, non athletics combined events use a row sum of times in each event, just allowing dispute events measured in time scale (or including subjective scores or using non continuous and non progressive scores). The idea behind the scoring tables used in athletics combined events is quite sophisticated. However, [1] argues it appears to be cursed with unacceptable bias, proposing some methods to correct them. Even so, until nowadays, nobody has been discussing that the difference among the individual scores is in fact the soul of the subject, once the final score is the sum (linear combination) of events scores. Our method uses a normalized mirrored-logarithmic function which facilitates the frec choice of its gradient (growth speed) according competition necds. In addition, it allows comparison of amateur and professional individuals, once it uses a robust reference point unlike average point, and it turns possible the use of scoring tables in competitions not globally disputed, for which top 100 lists could be corrupted by poor performances. The method is simple, interpretable, uniform over the events and enjoys the properties requested in [1] and [2]. Its purpose is not to compete with the proposals presented in [1] but lo popularize the use of scoring tables theory in competitions out of world of Athletics. To emphasize this, the method has been used successfully in Multiathlon since 2003, objectively comparing events so different like athletics, swimming, cycling, climbing, apnea and archery.